Hurthle cell carcinoma1. Issue 3 (14th August 2012) - Goffredo, Paolo; Roman, Sanziana A.; Sosa, Julie A.
Abstract BACKGROUND: Hurthle cell carcinoma (HCC) is an uncommon and more aggressive thyroid cancer. To date, there is a paucity of data at a population level. In this study, demographic, clinical, and pathologic characteristics of HCC were investigated and compared with other types of differentiated thyroid cancers (ODTCs). The authors also evaluated disease‐specific survival and compliance with American Thyroid Association (ATA) management guidelines from 2009. METHODS: The Surveillance, Epidemiology, and End Results (SEER) database from 1988 to 2009 was used to obtain data on patients with thyroid cancer. Data analyses were performed using chi‐square tests, analysis of variance, Kaplan‐Meier analysis, binary logistic regression, and Cox proportional hazards regression. RESULTS: In total, 3311 patients with HCC and 59, 585 patients with ODTC were identified. Compared with ODTC, HCC was more common among men (31.1% vs 23.0% for ODTC; P < .001) and among older patients (mean age, 57.6 years vs 48.9 years for ODTC; P < .001). Patients with HCC presented with higher SEER disease stage (P < .001), and their tumors were larger (36.1 mm vs 20.2 mm for ODTC; P < .001). Fewer patients underwent total thyroidectomy (P = .028). Both overall and disease‐specific survival were lower for patients with HCC (P < .001), and neither improved over the last 2 decades (P = .689). After adjustment, age ≥45 years, not undergoing surgery, and metastatic disease were strongly associated with a worse prognosis (hazard ratio >3.0). Compliance with recommended surgical treatment according to ATA guidelines was lower among patients with HCC aged ≥65 years (odds ratio [OR], 1.43; P = .002) and among unmarried patients (OR, 1.29; P = .004). Predictors of noncompliance with ATA guidelines for treatment with radioactive implants or radioisotopes were age ≥65 years (OR, 1.31; P = .017), diagnosis between 1988 and 1997, no surgery, and partial thyroidectomy (OR, 1.81, 19.48, and 4.02, respectively; P < .001). CONCLUSIONS: HCC has more aggressive behavior and compromised survival compared with ODTC. The current results indicated that it may be important to consider a different staging system or separate practice guidelines. Cancer 2013. © 2012 American Cancer Society.